Evidence-based post exercise recovery in combat sports: a narrative review - López-Laval, L.; Mielgo-Ayuso, J.; Terrados, N.; Calleja-Gonzalez, J. (The Journal of Sports Medicine and Physical Fitness, 2021)
INTRODUCTION: Some methods such as ergo nutritional aids, cooling or massage among others could improve recovery in combat sports (CS). The effects, doses, duration, and timing of these methods remains unknown. Nowadays, there is no clear consensus regarding the recovery strategies and it is necessary to understand the type of fatigue induced in CS and its underlying mechanisms. The main aim of this article is to review the update literature related to recovery strategies in CS. EVIDENCE ACQUISITION: A literature search was conducted following preferred reporting items for review statement on the topic of: "combat sports," "recovery," "nutrition," "fatigue," "ergogenic aids," "weight cutting" and "hydration." EVIDENCE SYNTHESIS: The initial search of the literature detected 369 articles about CS. Later, 307 were excluded after being determined unrelated to recovery or after failure to fulfill the inclusion criteria. Of the 80 included articles, 19 satisfied the final inclusion criteria. CONCLUSIONS: To optimize CS performance, adequate recovery is required during training and competition processes. Traditional ergo nutritional supplementation of carbohydrates and proteins combined. Besides, the consumption of evidence supported supplementation (green tea, beetroot gels, creatine or alkaline water) improve recovery processes. Further methods of recovery including physical (cold water immersion, massage or photobiomodulation) and physiological (types of active recovery, sleep and rest) therapies have also been shown useful. This narrative review elucidates the important role of recovery techniques in CS.